Modulation of biomimetic properties of cerium oxide nanoparticles by hypoxic tumor microenvironments: steering towards tumor specificity. (29th March 2018) - Sridharan, Preethi; Vinothkumar, G.; Pratheesh, Pooja; Babu, K. Suresh
Abstract : Cerium oxide nanoparticles exhibit selective cytotoxic and biomimetic antioxidant activity due to the redox transformation between Ce 3+ ↔ Ce 4+ states under tumor-like conditions. Abstract : The low oxygen tension characterizing the core glioblastomas (GBMs) and other solid tumors is known to cause a metabolic shift within tumors. This lowers the pH and simultaneously increases the ROS (O2 ˙ −, HO˙, H2 O2 etc., ) accumulation which eventually facilitates the tumor resistance to chemo/radiotherapy. Herein, we report the biomimetic antioxidant properties of cerium oxide nanoparticles (CNPs) under physiological and tumor microenvironment-like conditions in vitro using a GBM cell line. CNPs were synthesized in a single step combustion method and exhibited selective cytotoxicity under tumor microenvironment-like conditions. Furthermore, the peroxidase-like activity of the CNP nanoparticles was modulated by tumor microenvironment-like conditions (pH 6.5 and 1.5% O2 ) due to the redox transformation between the Ce 3+ ↔ Ce 4+ states of the cerium oxide nanoparticles under different conditions. When incubated with CNPs, a remarkable variation in the oxidative stress was observed from the measured MDA levels. Combined results from a peroxidase assay, MDA assay and TBARS assay revealed size and pH dependent activity which could have significant implications towards the tumor specific activity. The results are promising for the use of CNPs for tumor therapy and warrant further studies using both in vivo and in vitro models on their possible therapeutic potential.